DAMPAK PELATIHAN LITERASI KEUANGAN TERHADAP INKLUSI KEUANGAN PETANI DI KECAMATAN TUTUR KABUPATEN PASURUAN (The Impact of Financial Literacy Training on Financial Inclusion of Farmers in Tutur District, Pasuruan Regency) - Hidayat, Savitri Winawati; Ilmi, Evi Maf'idatul; Koesriwulandari, Koesriwulandari (Jurnal Ilmiah Sosio Agribis, 2025)
This study analyzes the impact of financial literacy training for young farmers in Tutur District, Pasuruan Regency, which aims to improve financial management capacity and access to formal financial products. The training was conducted by agricultural extension workers and financial practitioners. Data were collected through questionnaires, observations, and interviews with 35 young farmers (purposive sampling) and analyzed using multiple linear regression with variables of method, material, duration, and facilitator. The results showed: Training methods and facilitators have a significant effect on increasing financial inclusion of young farmers, Training material and duration have no significant impact, The model explains 88.5% of the variation in financial inclusion (11.5% is influenced by other factors). These findings highlight the importance of an interactive training approach and ongoing mentoring by extension workers. Financial literacy training is effective in encouraging access to formal finance, which can strengthen farming business development. Policy implications emphasize the need for post-training mentoring programs to maximize the impact of financial literacy.Keywords: financial literacy, financial inclusion, young farmers, agribusiness, agricultural training